Recurrent meningitis in childhood - Özdirim, Emire (The Turkish Journal of Pediatrics, 1981)
In this study, 53 cases (39 boys and 14 girls) with recurrent meningitis seen at Hacettepe Children's Hospital were evaluated. Six (11%) patients died and 12 (22%) showed neurological sequelae. Recurrences of meningitis ranged from 2 to 11 times. Head trauma (28 cases), infection (14 cases), subdural collection (2 cases), dermoidal sinus (2 cases), immunological deficiency (1 case), hemolytic anemia and splenectomy (1 case) and Mollaret meningitis (1 case) were the identifiable causes of recurrence. Pneumococcus was isolated in the CSF of 45% of the cases for which the culture was grown. Various methods to determine the cause of recurrence and appropriate treatment in addition to antibiotics were discussed.
Keywords: meningitis in childhood; recurrent meningitis